MEWUJUDKAN GURU DAN TENAGA KEPENDIDIKAN PAUD DAN DIKMAS YANG MULIA, PROFESIONAL, DAN SEJAHTERA UNTUK MEMBENTUK INSAN INDONESIA YANG BERKARAKTER - Abdoellah, Abdoellah (JIV-Jurnal Ilmiah Visi, 2017)
Educational practitioner and educational staff play an important role in reaching the national education objectives, including in non-formal education. Teachers of Kindergarten, Early Childhood Education, and Community Education are expected to provide all level of society with quality educational services. The purpose of this article is to describe various efforts which have already done and to be done by The Directorate of Teacher Development for Kindergarten, Early Childhood Education, and Community Education, particular in 2017. The article presents in detail priority programs such as (1) strengthening the roles of teachers and supporting educational staff, (2) developing the teachers and supporting educational staff of Early Childhood Education and Community Education, and (3) improving the quality of management of teachers and supporting educational staff of Early Childhood Education and Community Education. In addition, considering the exisiting and the future condition, a number of problems and threats are also mentioned with some alternative solutions suggested.